Analisis Karakter Mahasiswa Pelaku Wirausaha di Kota Batam - Wisnu Yuwono; Alva Hendi Muhammad (Politeknik Negeri Batam, 2014)
This study aims to identify the character of the university students as the actors of entrepreneurship in Batam and to develop the entrepreneur characters learning model for the university students to face ASEAN Economic Community (AEC) in the end of 2015. This research uses the descriptive analysis method with the case study approach in Batam city especially in Universitas Internasional Batam, involving 113 respondents using the purposive sampling method. Using the scoring analysis technic is used to draw a conclusion that the average characteristics of the university students as the actors of entrepreneurship in Batam have not meet the expectation since they are still in the moderate category, so the universities need to be more creative in fulfilling their role especially in the development of syllabus and curriculum for the learning process